Effect of direct seeding and transplanting method on the weed population / Amir Hafiz Azanan - Azanan, Amir Hafiz (Faculty of Plantation and Agrotechnology, 2019)
Rice is Malaysia most important staple food and also within the ASEAN country. In this century, weeds bring many problem in rice cultivation that cause in reduction of yield for every farmer. Most common weed problem is it would affect the rice growth, obstruct the harvesting process and reduces the quality of the grains obtained. Application of chemical control for controlling weeds still not effective to reduce weed population. This study was conducted to investigate the effect of direct seeding and transplanting method on the weed population and distribution. This study was carried out at Kampung Padang, postcode 13200 which were managed under Integrated Agricultural Development Area (IADA) Seberang Perai Utara, Pulau Pinang during month October 2018. Study comprised of two field of different planting method using rice variety, MR 263. Paddy transplanting with 20 x 20 cm² (centimeter square) distance and direct seeding by broadcasting in standing water. Method of area sampling for weed determination is by placed 1 m² (meter square) quadrat wire on 15 different place per paddy field, randomly. Components such as type of weed, percentage Frequency (F), weed density per meter square (D), percentage relative frequency (RF), percentage relative density (RD) and Importance Value Index (IVI) were calculated. Direct seeding field shows significantly higher distribution and more species of weed compared to transplanting field which IVI value of weed in direct seeding field consist of Cyperus haspan (6.1), Ipomea aquatica (4.2), Jussiaea linifolia (8.2), Monochoria vaginalis (14.8) and Sagittaria guayanensis (20.2) compared with transplanting field that consist of Leptochloa chinensis (8.2), Monochoria vaginalis (13.6) and Sagittaria guayanensis (31.6).